Media Dissemination of Road Sector Reforms - Mwale, Sam M. (World Bank, Washington, DC, 2012)
Over the past five years, the 'second liberalization' of Africa has liberalized the local media in turn. The explosion of media outlets and the diversity of their outreach provide excellent opportunities for the dissemination to, and ownership of development policies, programs, and projects by the stakeholders and beneficiaries. While the practice of participatory development in Africa is relatively new, the practice of using the media as a development tool, especially as a means of facilitating discussion, is even newer. Policymakers view exposing development programs and projects in the public domain via the media with some trepidation. This fear arises, not so much from a fear of public debate, as from the view that 'experts' already know all the answers, in the form of feasibility studies, technical and analytical reports, and participatory rural appraisals.